Thermal treatment of composite wastes for energy recovery - Vesna Alivojvodić; Slaviša Putić (Zaštita Materijala)
The expression waste-to-energy technologies is increasingly being used regarding waste reduction and utilization. Waste-to-energy technologies are procedures used to generate different forms of energy starting from a waste source. Considering that this pap waste, the previously mentioned procedures can be divided into mechanical, thermal and chemical treatment of composite waste. Thermal treatment processes provide a wide range of options to produce electricity, heat, oils, gases, fuels and chemicals starting waste. Some procedures are used for commercial purposes, while many are still being developed in laboratories or semi-industrial plants. The presented paper is focused to briefly review recent ld of thermal treatment of composite waste materials.